2019
DOI: 10.1093/ntr/ntz087
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation in Affordable Care Act Medicaid Expansion States Versus Non-expansion States

Abstract: Introduction Community health centers (CHCs) care for vulnerable patients who use tobacco at higher than national rates. States that expanded Medicaid eligibility under the Affordable Care Act (ACA) provided insurance coverage to tobacco users not previously Medicaid-eligible, thereby potentially increasing their odds of receiving cessation assistance. We examined if tobacco users in Medicaid expansion states had increased quit rates, cessation medications ordered, and greater health care uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…Despite these increased odds of smoking cessation medication orders among cancer survivors in expansion versus non-expansion states, we did not observe statistically significant differences in odds of quitting. These findings are in contrast to those of a previous study that found higher odds of quitting smoking among adult patients of CHCs in expansion states compared with those in non-expansion states; however, this prior study included the entire patient population and subanalyses for cancer survivors were not performed [ 20 ]. We postulate potential reasons for this finding.…”
Section: Discussioncontrasting
confidence: 93%
“…Despite these increased odds of smoking cessation medication orders among cancer survivors in expansion versus non-expansion states, we did not observe statistically significant differences in odds of quitting. These findings are in contrast to those of a previous study that found higher odds of quitting smoking among adult patients of CHCs in expansion states compared with those in non-expansion states; however, this prior study included the entire patient population and subanalyses for cancer survivors were not performed [ 20 ]. We postulate potential reasons for this finding.…”
Section: Discussioncontrasting
confidence: 93%
“…Another proven approach to increasing the use of cessation assistance is to reduce patient cost barriers 60 . Research has shown that when health insurance offers comprehensive cessation coverage without cost‐sharing, patients are more likely to participate in treatment 10,61–63 and succeed in quitting 62,63 . Rural PCPs could work with local stakeholders and policy makers either to extend such comprehensive coverage to rural residents or to offer no‐cost cessation services to uninsured patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another proven approach to increasing the use of cessation assistance is to reduce patient cost barriers. 60 Research has shown that when health insurance offers comprehensive cessation coverage without cost-sharing, patients are more likely to participate in treatment 10,[61][62][63] and succeed in quitting. 62,63 Rural PCPs could work with local stakeholders and policy makers either to extend such comprehensive coverage to rural residents or to offer no-cost cessation services to uninsured patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The late 2000s and early 2010s were a time of rapid expansion of coverage for tobacco dependence treatment (TDT) in state Medicaid programs; however, coverage continued to be variable, with most state plans excluding one or more evidence-based treatments (i.e., individual or group counseling, or FDA-approved medications). [13][14][15][16][17] For example, from 2009 to 2013, 15 states changed coverage for individual/group counseling; five states changed coverage for gum, patch, or lozenge; 14 states changed coverage for inhaler or spray, and six states changed coverage for bupropion or varenicline (see Appendix S1 for details). Medicaid recipients in states with comprehensive TDT coverage have higher quit rates 16,17 ; and enrollment expansions have increased rates of patient assistance and smoking cessation medication use.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies evaluating the effects of TDT coverage expansion among the general population of Medicaid recipients have had limitations, including focusing on just a single state, 18 or focusing on patients already receiving tobaccorelated treatment at community health centers. 17 It remains unclear whether expanded TDT coverage, on a national scale, is associated with increased TDT use for adult Medicaid beneficiaries with SUD.…”
Section: Introductionmentioning
confidence: 99%